Oxazaphosphorine bioactivation and detoxification: the role of xenobiotic receptors - Duan Wang; Hongbing Wang (Elsevier, 2012)
Oxazaphosphorines, with the most representative members including cyclophosphamide, ifosfamide, and trofosfamide, constitute a class of alkylating agents that have a broad spectrum of anticancer activity against many malignant ailments including both solid tumors such as breast cancer and hematological malignancies such as leukemia and lymphoma. Most oxazaphosphorines are prodrugs that require hepatic cytochrome P450 enzymes to generate active alkylating moieties before manifesting their chemotherapeutic effects. Meanwhile, oxazaphosphorines can also be transformed into non-therapeutic byproducts by various drug-metabolizing enzymes. Clinically, oxazaphosphorines are often administered in combination with other chemotherapeutics in adjuvant treatments. As such, the therapeutic efficacy, off-target toxicity, and unintentional drug-drug interactions of oxazaphosphorines have been long-lasting clinical concerns and heightened focuses of scientific literatures. Recent evidence suggests that xenobiotic receptors may play important roles in regulating the metabolism and clearance of oxazaphosphorines. Drugs as modulators of xenobiotic receptors can affect the therapeutic efficacy, cytotoxicity, and pharmacokinetics of coadministered oxazaphosphorines, providing a new molecular mechanism of drug-drug interactions. Here, we review current advances regarding the influence of xenobiotic receptors, particularly, the constitutive androstane receptor, the pregnane X receptor and the aryl hydrocarbon receptor, on the bioactivation and detoxification of oxazaphosphorines, with a focus on cyclophosphamide and ifosfamide.